A Libertarian Legitimacy for Mandatory Covid-19 Vaccination - Yudi Setiawan; Zaid Zaid; Nanik Prasetyoningsih; Mahbub Pasca Al Bahy (Fakultas Hukum Universitas Muhammadiyah Yogyakarta, 2022)
Since its inception, the 2019 coronavirus disease (Covid-19) outbreak has become a major health problem. At the same time, countries worldwide have been waiting for a Covid-19 vaccine to be sufficiently available. When the Covid-19 vaccine became available, several countries began to adopt mandatory Covid-19 vaccination policies. However, mandatory Covid-19 vaccination has received strong opposition from the start. Rejections have emerged from various parties, including from libertarians. The researcher observes that the current research attempting to analyze the mandatory Covid-19 vaccination still revolves around the perspective of human rights and utilitarianism. Then, this study aims to explore and find out how the libertarian perspective toward mandatory vaccination. Normative research methods with conceptual and comparative approaches were used in this study. After analyzing secondary data sources with prescriptive analysis methods, this study finally succeeded in finding that mandatory Covid-19 vaccination has its place, legitimacy, and justification on the ideological side of libertarianism. It is because libertarians accept that the government may require a mandatory vaccination program against Covid-19. In addition, due to the libertarian framework, the government is still justified in enforcing coercive policies that violate the rights of certain individuals if the policy is necessary to avoid greater harm to others.